Android Apps Security Evaluation System in the Cloud - Hao Wang; Tong Zhang; Jie Wang (EAI Endorsed Transactions on Cloud Systems, 2016)
It is an uncertain problem that evaluating the security of Android Apps. We can’t be sure of the danger with sensitive permissions in an individual of Apps. Permissions are an important factor in security decisions of Apps. For the Apps security evaluation, the paper proceed from the Android permission mechanism, proposes a classified dynamic security evaluation method. Apps security evaluation system include the large-scale permissions capturing and classification risk evaluation algorithm. The system could find the minimum permissions which are the common features of Apps. The minimum permissions can be dynamically changed according to different classified Apps. We adopt Euclidean distance-based similarity calculation algorithm to evaluate risk. The difference value determines the APP’s malicious risk. Experiments prove that the system has reference value to the APP security assessment.